External Dimension of the European Union Environmental Policy- Selected Legal Issues - Kalicka-Mikołajczyk, Adriana (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
Most environmental problems have a transboundary nature and often a global scope, and they can only be addressed effectively through international cooperation. For this reason, the Lisbon Treaty establishes that one of the key objectives of the European Union (EU) policy on the environment is to promote measures at an international level to deal with regional or worldwide environmental problems, and in particular combating climate change. The paper focuses on two issues: firstly, on the evolution of the EU competences in the area of environment and secondly on the extent and the nature of the EU competence in environmental matters.
Keywords: Unia Europejska; polityka środowiskowa; zmiany klimatyczne